Effects of Water Acidification on Senegalese Sole Solea senegalensis Health Status and Metabolic Rate: Implications for Immune Responses and Energy Use - Machado, Marina; Arenas, Francisco; Svendsen, Jon C.; Azeredo, Rita; Pfeifer, Louis J.; Wilson, Jonathan M.; Costas, Benjamín (Frontiers in Physiology, 2020)
Increasing water CO2, aquatic hypercapnia, leads to higher physiological pCO2 levels in fish, resulting in an acidosis and compensatory acid-base regulatory response. Senegalese sole is currently farmed in super-intensive recirculating water systems where significant accumulation of CO2 in the water may occur. Moreover, anthropogenic releases of CO2 into the atmosphere are linked to ocean acidification. The present study was designed to assess the effects of acute (4 and 24h) and prolonged exposure (4 weeks) to CO2 driven acidification (i.e. pH 7.9, 7.6 and 7.3) from normocapnic seawater (pH 8.1) on the innate immune status, gill acid-base ion transporter expression and metabolic rate of juvenile Senegalese sole. The acute exposure to severe hypercapnia clearly affected gill physiology as observed by an increase of NHE3b positive ionocytes and a decrease of cell shape factor. Nonetheless only small physiological adjustments were observed at the systemic level with 1) a modulation of both plasma and skin humoral parameters and 2) an increased expression of HIF-1 expression pointing to an adjustment to the acidic environment even after a short period (i.e. hours). On the other hand, upon prolonged exposure, the expression of several pro-inflammatory and stress related genes was amplified and gill cell shape factor was aggravated with the continued increase of NHE3b positive ionocytes, ultimately impacting fish growth. While these findings indicate limited effects on energy use, deteriorating immune system conditions suggest that Senegalese sole is vulnerable to changes in CO2 and may be affected in aquaculture where a pH drop is more prominent. Further studies are required to investigate how larval and adult Senegalese sole are affected by changes in CO2.